Human flourishing through dance practice. - Vartanian, Meghedi; Khorsandi, Shahrzad; Sancho Escanero, Luisa; Acedo-Carmona, Cristina; Christensen, Julia; Sancho Escanero, Luisa (Routledge, 2022)
Empirical evidence from affective neuroscience and experimental psychology reveals that individuals who consider themselves “happy” and “self-actualized”, generally, have three important components in their life: they have regular experiences of hedonia (pleasure/positive affect), eudemonia (life meaning) and agency (a feeling of engagement/being in control of one’s life) (Seligman et al., 2005; Kringelbach and Berridge, 2009). Life does not always afford easily accessible opportunities to experience these three components and to flourish as a person. Resilience, the cognitive capacity to deal with adversity (Wu et al., 2013), can include seeking out opportunities where pleasure, eudemonia and agency can be experienced, when they are not offered by everyday life. The arts, and, in particular, dance practice, are contexts in which opportunities for experiencing these three components of a flourishing life can be experienced regularly. For this, mindful practices that foster empathy and agency need to
https://www.routledge.com/our-products/open-access-books/publishing-oa-books/chapters?srsltid=AfmBOooRj1x7xAjYaQ9TTG0Xat7znCZHPncQacDRkuvTOT9lQ1TCOeEl
Keywords: Danza - Aspectos psicológicos; Human interactions; Dance; Humanity; Prosocial behavior